2020
DOI: 10.1089/mdr.2019.0124
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Antiseptics and Disinfectants of Planktonic and Biofilm-Associated Forms of Corynebacterium striatum

Abstract: Disinfection and antisepsis are of primary importance in controlling nosocomial infections and outbreaks by pathogens expressing multiple resistance to antimicrobial agents (multidrug-resistant [MDR]) used in therapy. Nowadays, infections related to health services (HAIs) due to MDR and multidrug-susceptible (MDS) Corynebacterium striatum should not be underestimated, including patients using invasive medical devices. The virulence potential of C. striatum needs further investigation. Currently, susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
(81 reference statements)
0
10
0
1
Order By: Relevance
“…A recent report revealed that some dominant C. striatum clones showed resistance to some widely used biocides at different levels, including high-level disinfectants (such as glutaraldehyde) [ 23 ]. Therefore, the sensitivity of dominant C. striatum isolates from different hospitals to commonly used biocides should be further evaluated, and the selective use of effective biocides should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report revealed that some dominant C. striatum clones showed resistance to some widely used biocides at different levels, including high-level disinfectants (such as glutaraldehyde) [ 23 ]. Therefore, the sensitivity of dominant C. striatum isolates from different hospitals to commonly used biocides should be further evaluated, and the selective use of effective biocides should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is the qacEdelta1 gene, which confers resistance to quaternary ammonium compound biocides. Biocide resistance was reported and associated with biofilms by Souza et al (2020) [ 28 ]. On the other hand, the sul gene and the qacEdelta1 gene are frequently seen in class 1 integrons.…”
Section: C Striatum Resistomementioning
confidence: 99%
“…C. striatum strains expressing varied MDR profiles have been identified as the etiologic agent of various types of both nosocomial and non-healthcare associated infections reported in industrialized and developing countries [ 25 , 27 ]. Recently, resistance to antiseptic and disinfectants such as glutaraldehyde (GA) has also been reported for C. striatum [ 28 ]. Accordingly, medical surveillance programs should include control strategies to decrease potential risk factors of nosocomial infections and outbreaks due to C. striatum .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C. striatum strains get more aggressive in the presence of invasive medical devices, including catheters and endotracheal tubes. Consequently, the formation of bacterial biofilms leads to an increase in healthcare costs, extended hospitalization, and presumably the spread of antibiotic resistance genes [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%